Prosodic and Topical Variety in Khaqanis' âRubaies - احمد غنی‌پور ملکشاه; مهدی صراحتی جویباری (مطالعات زبانی و بلاغی)
For centuries âRubaiâ Because of its traits comparing âwith other forms of poetry has always been considered by âliterary men. One of those traits was having numerous and âvarious meters. Besides, Rubai as a form which can âencompass various topics and contents was always âconsidered by most poets. With due attention to that matter, âkhaqanis' rubaies are scrutinized with a view to prosodic and âtopical variety i.e., most occurring and prevalent meters and âtopics in khaqanis' rubaies â accompanied by statistical âinformation â is rendered here. Khaqanie's rubaies are also âscrutinized with a view of rhyme and Radif.â